2008
DOI: 10.1093/jxb/ern226
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Xhdsi-1VOC, a novel member of the vicinal oxygen chelate (VOC) metalloenzyme superfamily, is up-regulated in leaves and roots during desiccation in the resurrection plant Xerophyta humilis (Bak) Dur and Schinz

Abstract: The annotation of novel plant genes is frequently based on sequence and structural similarity to known protein motifs. Understanding the biological function of these genes is dependent on identifying conditions under which they are activated, however. The resurrection plant, Xerophyta humilis is a good model system for identifying and characterizing genes which are important for desiccation tolerance. Desiccation induced-1 (dsi-1VOC), a previously uncharacterized plant gene, is up-regulated during desiccation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…Because homologous VOC genes were mainly related to desiccation and drought stress, there are fewer reports regarding their function under other types of abiotic stress (Mulako et al, 2008; Mustafiz et al, 2014). B. napus were treated with drought stress to study the BnaVOC expression pattern under drought stress conditions; to determine whether the BnaVOC s expression is linked to lipid formation under drought condition, high oil content and low oil content B. napus were used, and the analysis was performed with qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Because homologous VOC genes were mainly related to desiccation and drought stress, there are fewer reports regarding their function under other types of abiotic stress (Mulako et al, 2008; Mustafiz et al, 2014). B. napus were treated with drought stress to study the BnaVOC expression pattern under drought stress conditions; to determine whether the BnaVOC s expression is linked to lipid formation under drought condition, high oil content and low oil content B. napus were used, and the analysis was performed with qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, however, all the antioxidant enzymes were able to maintain activity when extracted from tissues with RWC 10%. This has been reported to be the case in leaves of this and other resurrection plants such as Xerophyta humilis, Eragrostis nindensis, Craterostigma wilmsii and Myrothanmus flabellifolius and is believed to be important in quenching of ROS in recovery of metabolism upon rehydration; the same enzymes being used during rehydration rather than reliance on de novo synthesis of enzymes occurring once full hydration is achieved (Farrant 2000(Farrant , 2007Mowla et al 2002;Illing et al 2005;Mulako et al 2008). While our data indicate that a decline (or relative maintenance) in extent of enzyme activity occurs during drying in roots of X. viscosa, the opposite is true in leaves …”
Section: Antioxidant Analysismentioning
confidence: 91%
“…We report here on use of such a system to study the effects of desiccation on roots of this resurrection plant. One of the key protective mechanisms induced during desiccation involves the upregulation of antioxidant activity (Farrant 2000(Farrant , 2007Mowla et al 2002;Moore et al 2004;Kranner and Birtic 2005;Illing et al 2005;Moore et al 2009;Mulako et al 2008). This involves the ''classical'' (Kranner and Birtic 2005) or ''housekeeping'' antioxidants (Illing et al 2005), so called because they are present in all plants and are crucial to maintenance of cellular homeostasis under dayto-day conditions and in protection against a myriad of abiotic and biotic stresses (for an overview, see Estner and Oswald, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is intriguing to speculate that the variant topology represented by these two proteins is likely to play a role. Other new extradiol dioxygenases have been recently identified that may represent yet additional topological variants evolved to accommodate functional requirements via mixing and matching of subdomain modules [24,25]. …”
Section: The Vicinal Oxygen Chelate (Voc) Superfamily: Mixing and Matmentioning
confidence: 99%